Polemik Masa Depan Ekonomi Islam - Ubaidillah, Ahmad (ITB AAS INDONESIA Surakarta, 2024)
This article aims to elaborate the Islamic economic thoughts of Muhammad Nejatullah Siddiqi on the future direction of Islamic economics along with the responses of a number of Islamic economists. What are Siddiqi's Islamic economic thoughts that have become polemics among Islamic economists is the question that will be answered in this article. This research is a library research, namely a research process that reviews literature and analyzes relevant topics. In collecting data, the author utilizes journals, books, dictionaries, magazines, and other library sources. The analysis method used in this study is the hermeneutic method, which means interpreting, explaining, interpreting, and translating these data sources. The results of the study show that both Rodney Wilson, Tariqullah Khan, Laurent Weill and Noureddine Krichene found harmony with Muhammad Nejatullah Siddiqi's ideas about what should be done for the progress of Islamic economics. Although harmony in consensus and dominant views is common, there are many differences of opinion among Islamic economists regarding the diagnosis of this problem, as well as regarding its solution.